Evaluation of Risk Factors for Vertebral Compression Fracture after Carbon-Ion Radiotherapy for Primary Spinal and Paraspinal Sarcoma. (26th July 2017) - Matsumoto, Yoshihiro; Shinoto, Makoto; Endo, Makoto; Setsu, Nokitaka; Iida, Keiichiro; Fukushi, Jun-Ichi; Kawaguchi, Kenichi; Okada, Seiji; Bekki, Hirofumi; Imai, Reiko; Kamada, Tadashi; Shioyama, Yoshiyuki; et al.
Abstract : Background and Purpose . Carbon-ion radiotherapy (C-ion RT) was effective therapy for inoperable spinal and paraspinal sarcomas. However, a significant adverse event following radiotherapies is vertebral compression fractures (VCFs). In this study, we investigated the incidence of and risk factors for post-C-ion RT VCFs in patients with spinal or paraspinal sarcomas. Material and Methods . Thirty consecutive patients with spinal or paraspinal sarcomas treated with C-ion RT were retrospectively reviewed. Various clinical parameters and the Spinal Instability Neoplastic Score (SINS) were used to evaluate the risk factors for post-C-ion RT VCFs. Results . The overall incidence of VCFs was 23% (median time: 7 months). Patients with VCFs showed a markedly higher SINS score (median value, 9 points) than those without VCF (5 points). The area under the receiver operating characteristic curve for the SINS score was 0.88, and the optimum SINS cut-off score was 8 points. The cumulative incidence of VCFs at 1 year was 9% for patients with a SINS score under 8 points, versus 80% for those with a SINS score of 8 points or higher (p < 0.0001 ). Conclusions . In patients with a SINS score of 8 points or higher, referral to a spine surgeon for stabilization and multidisciplinary discussion is appropriate.